ISSUES OF ACCESS TO AND USE OF INFORMATION-BY-INFORMATION INTERMEDIARIES - Umidbek Nurullaev (Web of Journals Publishing, 2025)
This article examines the legal issues surrounding the right of information intermediaries to access and use information within the framework of Uzbekistan’s civil law. Although civil law traditionally governs property and non-property relations, the activities of information intermediaries such as searching for, obtaining, processing, and disseminating information are carried out within the scope of civil legal relations. The author analyzes theoretical and practical approaches to defining the legal status of intermediaries in accessing data, including their role in forming and regulating information flows. The article also evaluates comparative legal models from the United States, the European Union, Germany, France, and Russia. It is argued that information access rights are often limited by proprietary and contractual frameworks, which may conflict with personal non-property rights, such as the right to receive information. Based on this analysis, the author proposes a new hybrid legal approach recognizing intermediaries as both private actors and entities responsible for upholding public interest, ensuring a balance between ownership rights and freedom of information in digital environments.
Keywords: Information intermediary, civil law, information access, content filtering, digital rights, public interest, proprietary rights, user rights, CDA §230, EU Directive 2000/31/EC, DMCA, data platforms, legal regulation, information freedom, transparency.